Comparative Description Of Anthropometric Indicators Of Nutritional Strategy In Practitioners With An Ectomorph Body Structure - U.Sh.Valikhanov (Global Scientific Publishing, 2024)
This study demonstrates the impact of proper nutrition on the engaging form of athletic gymnastics, a healthier type of gymnastics. Observations were conducted on second-year students of the Faculty of Physical Culture of Andijan State University. Through the study, the study described how the effectiveness of athletic exercise in determining the anthropometric performance of students depends on the proper organization of nutrition. The importance of supplemental nutrition for ectomorphic individuals by body type has been demonstrated
Keywords: Athletic gymnastics; ectomorph; mesomorph; creatine